2019
DOI: 10.1002/ajoc.201900550
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Trifluoromethyl‐Substituted Cyclopropanes via Inorganic Base‐Mediated Cycloaddition Reactions

Abstract: An efficient and concise synthesis of various trifluoromethyl-substituted cyclopropanes from a variety of dienes and enynes in the presence of cheap inorganic base potassium phosphate has been reported. This methodology features high yields (up to 89%), wide substrate scope and excellent functional group tolerance (25 examples).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…30% yield (Scheme ). The authors also found that inorganic bases significantly increased the reaction yield, and best results were obtained with potassium phosphate. Having an optimized procedure in hand, the authors studied the scope of the reaction by preparing 25 diverse CF 3 -cyclopropanes of type 82 – 84 in 62–85% yield.…”
Section: Chemical Propertiesmentioning
confidence: 92%
See 1 more Smart Citation
“…30% yield (Scheme ). The authors also found that inorganic bases significantly increased the reaction yield, and best results were obtained with potassium phosphate. Having an optimized procedure in hand, the authors studied the scope of the reaction by preparing 25 diverse CF 3 -cyclopropanes of type 82 – 84 in 62–85% yield.…”
Section: Chemical Propertiesmentioning
confidence: 92%
“…30% yield (Scheme 17). 36 The authors also found that inorganic bases significantly increased the reaction yield, and best results were obtained with potassium phosphate. Having an optimized procedure in hand, the authors studied the scope of the reaction by preparing 25 [3 + 2]-cycloaddition between in situ generated CF 3 CHN 2 (1) and electron-deficient allenes appeared in 2014 by Ma and co-workers (Scheme 18).…”
Section: Preparationmentioning
confidence: 94%
“…Dienes 61 and eneynes were converted into trifluoromethyl‐substituted cyclopropanes [28] 63 upon treatment with a solution of excess trifluoromethyl diazomethane 62 (6 equiv) in toluene in the presence of catalytic amounts of potassium phosphate (Scheme 22). Although the reaction tolerates several functionalities (thiophene, benzothiophene, indole, cyano), it is not diastereoselective.…”
Section: Fluoro‐ Monofluoromethyl‐ Difluoromethyl‐ and Trifluoromementioning
confidence: 99%
“…12 Wang et al have also reported an example of cycloaddition of enyne with CF 3 CHN 2 in the presence of 10 mol% K 3 PO 4 (Scheme 1g). 13 In 2019, Wang developed a novel approach for the synthesis of CF 3 -containing alkynylcyclopropanes by the reaction of trifluoromethyl activated 1,3enynes with sulfur ylides (Scheme 1h). 14 Generally, the cycloaddition reaction of CF 3 CHN 2 (or CH 2 N 2 ) with alkenes can furnish CF 3 -containing cyclopropanes or CF 3 -containing pyrazolines depending on the structure of the alkenes and reaction conditions employed.…”
Section: Introductionmentioning
confidence: 99%